2019
DOI: 10.1186/s12944-019-0985-8
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism and its association with dyslipidemia risk in children and adolescents: a cross-sectional study

Abstract: BackgroundInformation on the association between iron metabolism and dyslipidaemia in children is limited. Thus, this study aims to evaluate the iron metabolic status of children with different body mass index (BMI) and to examine the association between iron metabolism and dyslipidaemia risk.MethodIn total, 1866 children and adolescents aged 7–18 were enrolled in this study, including 912 boys and 954 girls. In this cross-sectional study, parameters for anthropometry, lipids and iron metabolism including tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
(43 reference statements)
5
20
0
Order By: Relevance
“…The relationship between iron status and blood lipids is similarly ambiguous. Some epidemiological studies found that blood iron is lower in hyperlipidemic patients [ 42 ] and that blood ferritin is negatively associated with LDL cholesterol [ 13 ]. Very likely related, elevated iron status is negatively associated with coronary artery disease in both observational and MR studies [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between iron status and blood lipids is similarly ambiguous. Some epidemiological studies found that blood iron is lower in hyperlipidemic patients [ 42 ] and that blood ferritin is negatively associated with LDL cholesterol [ 13 ]. Very likely related, elevated iron status is negatively associated with coronary artery disease in both observational and MR studies [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the aim of better recognition of the regulatory mechanisms of insulin signaling pathways, many biomolecules and their mutual interaction have been investigated so far [6][7][8]. Recent advances in that field pointed out the relationship between several iron homeostasis biomarkers and IR [9][10][11][12][13][14]. However, those results are inconclusive doubting whether they act via different and independent pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of studies on the associations between iron homeostasis biomarkers and IR were conducted in the adult population [9][10][11] and reported discrepant results, such researches in youngsters are scarce [12][13][14], especially in late adolescents, as a vulnerable population group. Hence, having in mind a smaller number of studies conducted in the pediatric population compared to adults, as well as the inconclusive results considering this issue, we aimed to gain a deeper knowledge into the complex pathophysiological mechanisms related to IR.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, transgenic mice deficient in the human apoA-5 had strongly elevated triglyceride levels [24]. Alternatively, the PCSK7 could regulate lipid concentrations due to its participation in iron metabolism via the shedding of the human transferrin receptor-1 (hTfR1) [25][26][27]. This receptor is associated with inflammation and oxidative stress, processes that lead to atherosclerosis and other cardiovascular diseases [28].…”
Section: Discussionmentioning
confidence: 99%